Psychic Phenomena and the Brain: Exploring the Neuropsychology of Psi by Bryan J. Williams - Mörck, Nemo C. (Journal of Scientific Exploration, 2016)
Although few of us worry about whether our brain is too moist most agree with the physician Hippocrates who remarked that all experiences are intimately associated with the state of our brains. Whether this is because they all do, in fact, derive directly from the brain is however an unresolved question. Modern neuroscience assume that all experiences derive from brain activity. Some phenomena are however not easily explained by cotemporary neuroscience, and the brain might function as a kind of filter to consciousness (Kelly et al. 2007). Regardless of which perspective will eventually turn out to be right parapsychologists need to consider the brain in their theories. Are psi phenomena more likely to occur in a specific brain state? Do psychic claimants’ brains differ from others? Such questions are addressed in Bryan Williams’ ambitious, interesting, and concise monograph. Those that have read Williams’ articles cannot help but be impressed by his knowledge of the literature. Like his mentor, the late William Roll, he seem to be familiar with old literature concerning psychical research, modern neuroscience, and everything in between. About 19 of the monograph’s 135 pages (including an useful index) consist of references. Roll and Williams have previously reviewed the literature (e.g., Roll & Williams 2010; Williams, 2011, 2012, 2015; Williams & Roll 2008), and the monograph seem to derive primary from their articles. Given the limited space, there are naturally some omissions, but the monograph is readable and wide-ranging. Since the monograph is meant to make research accessible to curious laymen Williams initially explains the meaning of all terms, and provide a brief historical review of parapsychological research. In addition, he highlights the results of meta-analyses whose results suggest that psi exist (cf. Kennedy 2013). However, his review includes little about the criticism that the research has attracted, but Williams’ focus is on psychic phenomena and the brain. In addition, his intention is only to give an overview of key findings.